Biomarker-guided Intervention to Prevent Acute Kidney Injury After Major Surgery: The Prospective Randomized BigpAK Study. Issue 6 (June 2018) - Göcze, Ivan; Jauch, Dominik; Götz, Markus; Kennedy, Pascal; Jung, Bettina; Zeman, Florian; Gnewuch, Carsten; Graf, Bernhard M.; Gnann, Wolfgang; Banas, Bernhard; Bein, Thomas; Schlitt, Hans J.; et al.
Abstract : Objective: To determine the impact of renal biomarker–guided implementation of the Kidney Disease Improving Global Outcomes (KDIGO) care bundle on the incidence of acute kidney injury (AKI) after major noncardiac surgery in a single-center unblinded randomized clinical trial. Background: Early optimization of volume status and discontinuation of nephrotoxic medication before the occurrence of AKI may be the crucial step to reduce preventable AKI. Methods: The urinary biomarker−triggered KDIGO care bundle (early optimization of fluid status, maintenance of perfusion pressure, discontinuation of nephrotoxic agents) was compared to standard intensive care unit (ICU) care in 121 patients with an increased AKI risk after major abdominal surgery that was determined by urinary biomarker (inhibitor of metalloproteinase-2 × insulin-like growth factor–binding protein 7) >0.3. Incidence of overall AKI, severity of AKI, length of stay, major kidney events at discharge, and cost effectiveness were evaluated. Results: The overall stages of AKI were not statistically different between the 2 groups, but in patients with inhibitor of metalloproteinase-2 × insulin-like growth factor–binding protein 7 values of 0.3 to 2.0 a subgroup analysis demonstrated a significantly reduced incidence of AKI 13/48 (27.1%) in the intervention group compared to control 24/50 (48.0%, P = 0.03). Incidence of moderate and severe AKI ( P = 0.04), incidence of creatinine increase >25% of baseline value ( P = 0.01), length of ICU, and hospital stay ( P = 0.04) were significantly lower in the intervention group. Intervention was associated with cost reduction. There were no significant differences regarding renal replacement therapy, in-hospital mortality, or major kidney events at hospital discharge. Conclusions: Early biomarker-based prediction of imminent AKI followed by implementation of KDIGO care bundle reduced AKI severity, postoperative creatinine increase, length of ICU, and hospital stay in patients after major noncardiac surgery. Abstract : Supplemental Digital Content is available in the text